2016
DOI: 10.1097/jan.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction in High School Students in Turkey and Multivariate Analyses of the Underlying Factors

Abstract: The aim of this study is to examine the Internet addiction among adolescents in relation to their sociodemographic characteristics, communication skills, and perceived familial social support. This cross-sectional research is conducted in the high schools in some city centers, in Turkey, in 2013. In this study, cluster sampling was used. In each school, a class for each grade level was randomly selected, and all the students in the selected classes were included in the sample. One thousand seven hundred forty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 30 publications
5
22
3
3
Order By: Relevance
“…Better coping mechanisms and greater resilience in late adolescence could explain the lower risk behaviour with age among the females (Amaro et al, 2001;Hess and Richards, 1999). Our observation of a higher risk of PIU for vocational school students than for those attending a lyceum is similar to what observed in the Italian study by Poli (Poli and Agrimi, 2012), and in other studies (Kilic et al, 2016;Yen et al, 2008). In Italy, vocational school students generally come from families with a low socio-economic status, a characteristic that has been associated with higher PIU risk ( Yen et al, 2007Yen et al, , 2008Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Better coping mechanisms and greater resilience in late adolescence could explain the lower risk behaviour with age among the females (Amaro et al, 2001;Hess and Richards, 1999). Our observation of a higher risk of PIU for vocational school students than for those attending a lyceum is similar to what observed in the Italian study by Poli (Poli and Agrimi, 2012), and in other studies (Kilic et al, 2016;Yen et al, 2008). In Italy, vocational school students generally come from families with a low socio-economic status, a characteristic that has been associated with higher PIU risk ( Yen et al, 2007Yen et al, , 2008Zhang et al, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…This is in agreement with our results that highlights the significant association between poor family relationships and increased risk of IA (OR=1.9; 95% CI: 2.2-3.9). Correspondingly, Kilic et al [17] indicated that IA was uncommon among those having good family relations and enjoying family support.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are also consistent with the results of two studies in India, which reported that 46.8% and 44.6% of the respondents had IA of whom 0.5 and 3.07% were severe IAs, respectively [23,24] . Several studies in Iran, Turkey, and Tunisia found that 16.9, 18.8, and 28.7% of the respondents had IA [3,17,25] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hoy en día los adolescentes están más involucrados, en comparación con los adultos, por ejemplo, en el uso de internet (Blinka et al, 2014;Kilic, Avci, & Uzuncakmak, 2016). Además, la evidencia disponible refiere que los adolescentes son más propensos a la AI como una forma de mantener y/o aumentar su círculo social (Smahel et al, 2012); en ese sentido, serían el grupo etario con mayor acceso a internet (Kuss, Griffiths, Karila, & Billieux, 2014).…”
Section: Introductionunclassified